2010
DOI: 10.1002/tea.20401
|View full text |Cite
|
Sign up to set email alerts
|

College students' temporal‐magnitude recognition ability associated with durations of scientific changes

Abstract: The purpose of this study was to explore college students' recognition of temporal magnitudes associated with durations of scientific changes through construct validation of a 30‐item instrument. We administered the instrument to 514 students from 10 higher education institutions in the United States. Among them, 419 students took the instrument at the end of science courses. The remaining 95 students took the instrument before and after a course on cosmic evolution, and additionally answered whether they knew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…Conversely, Lee et al (2011) found that the ability to estimate an event's temporal duration (magnitude) is weakly correlated with whether students said they knew the event's duration or guessed. Upper division undergraduate majors in biology or geology are only marginally better than lower division undergraduates (Catley and Novick, 2009) at estimating the absolute placement of biological and geological events in Earth's history, even though the nature of their estimation errors differs.…”
Section: Impact Of Subject Matter Knowledge On Magnitude Estimationmentioning
confidence: 93%
See 2 more Smart Citations
“…Conversely, Lee et al (2011) found that the ability to estimate an event's temporal duration (magnitude) is weakly correlated with whether students said they knew the event's duration or guessed. Upper division undergraduate majors in biology or geology are only marginally better than lower division undergraduates (Catley and Novick, 2009) at estimating the absolute placement of biological and geological events in Earth's history, even though the nature of their estimation errors differs.…”
Section: Impact Of Subject Matter Knowledge On Magnitude Estimationmentioning
confidence: 93%
“…Unlike the spatial magnitude studies, there is no good empirical evidence of the existence of a common temporal metric akin to the human body (Delgado, 2013b). Only a few temporal scale magnitude studies include events that occur on human timescales (Lee et al, 2011;Delgado, 2013b;Jolley et al, 2013;Cheek, 2012Cheek, , 2013aCheek, , 2013bCheek, , 2016, so the potential value of any familiar, embodied event, such as day, year, or generations, is unclear.…”
Section: Standard and Nonstandard Units As Magnitude Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome is that any associated scientific events that occur on timescales using such numbers become misrepresented. Lee et al [21] also found that students tended to overestimate durations of time for large temporalmagnitude categories; however, students also tended to overestimate durations of time smaller than one millisecond. In related work, Tretter et al [76] explored students' conceptions of spatial scales and noticed students had difficulty providing accurate sizes of objects at the microscopic scale.…”
Section: Geological Timementioning
confidence: 99%
“…All physical science disciplines require their learners to possess some grasp of time-be it the time required for an event to happen, or for change to occur [21]. Time is inherent in order to grasp Darwin's theory of evolution, piece together Earth's geological history, approach the concept of climate change, or predict the eventual death of our Sun.…”
Section: A the Missing Linkmentioning
confidence: 99%